Nonlinear association between TyG-BMI and MAFLD: A cross-sectional study - Qiuping Wang; Yuan Su; Jing Niu; Yan Wang; Liping Liu; Yanhong Hao (PLoS ONE, 2025)
Background The relationship between the triglyceride glucose-body mass index (TyG-BMI) and the incidence of metabolic associated fatty liver disease (MAFLD) is a trending research area. This association is highly important in the realms of healthcare and public health. Objective To explore the impact of TyG-BMI on MAFLD and its contribution to the evolution of diverse phenotypes of fatty liver. Methods In this cross-sectional study, curve fitting was used to assess the relationships between TyG-BMI and MAFLD as well as different MAFLD phenotypes, and multivariate ordinal logistic regression methods were employed to explore the stability of these relationships. Results Curve fitting revealed a nonlinear relationship between TyG-BMI and MAFLD, with a critical threshold of approximately 176.78. Similar relationships were observed between TyG-BMI and different fatty liver phenotypes. Multivariate logistic regression revealed that the TyG-BMI was independently associated with different fatty liver phenotypes (nonfibrotic MAFLD odds ratio (OR) = 11.29; 95% confidence interval (CI) = 8.38–15.21, p < 0.001; fibrotic MAFLD OR = 37.24, 95% CI = 25.92–53.51, P < 0.001). Even after full variable adjustment, this relationship remained stable (nonfibrotic MAFLD OR = 5.99, 95% CI = 3.25--11.06, P < 0.001; fibrotic MAFLD OR = 5.24, 95% CI = 2.28--12.06, P < 0.001). Correlation analysis revealed a positive correlation between TyG-BMI and CAP (correlation coefficient, 0.60) and a weak positive correlation with SWE (correlation coefficient, 0.29). Conclusions The TyG-BMI manifests a nonlinear relationship with the risk of developing distinct MAFLD phenotypes, suggesting its utility as a pivotal metric in the formulation of screening and preventive strategies for MAFLD.